Acoustic analysis of oropharyngeal swallowing using Sonar Doppler - Soria, Franciele Savaris; da Silva, Roberta Gonçalves [UNESP]; Furkim, Ana Maria (Elsevier, 2016)
Introduction: During the aging process, one of the functions that changes is swallowing. These alterations in oropharyngeal swallowing may be diagnosed by methods that allow both the diagnosis and biofeedback monitoring by the patient. One of the methods recently described in the literature for the evaluation of swallowing is the Sonar Doppler. Objective: To compare the acoustic parameters of oropharyngeal swallowing between different age groups. Methods: This was a field, quantitative, study. Examination with Sonar Doppler was performed in 75 elderly and 72 non-elderly adult subjects. The following acoustic parameters were established: initial frequency, first peak frequency, second peak frequency; initial intensity, final intensity; and time for the swallowing of saliva, liquid, nectar, honey, and pudding, with 5- and 10-mL free drinks. Results: Objective, measurable data were obtained; most acoustic parameters studied between adult and elderly groups with respect to consistency and volume were significant. Conclusion: When comparing elderly with non-elderly adult subjects, there is a modification of the acoustic pattern of swallowing, regarding both consistency and food bolus volume.
Keywords: Deglutition; Elderly; Evaluation